Contrasting Impacts of Three Extreme El Niños on Double ITCZs over the Eastern Pacific Ocean - Yinlan Chen; Li Yan; Gen Li; Jianjun Xu; Jingchao Long; Shaojun Zheng (Atmosphere, 2021)
In the recent four decades, there were three record-breaking El Niño events: 1982/1983, 1997/1998, and 2015/2016 events. A double intertropical convergence zone (ITCZ) pattern distinctively emerges over the eastern Pacific Ocean during boreal spring. Based on reanalysis (ERA-Interim) during 1979–2018, this study examines how these three extreme El Niños modulate such double ITCZs. The 1982/1983 and 1997/1998 El Niños moved both northern and southern ITCZs equatorward to form an individual and broad equatorial ITCZ. In contrast, the regulation of 2015/2016 El Niño was unique with a strengthened southern ITCZ to form a symmetric double-ITCZ. The above differences can be attributed to the different meridional structures of sea surface temperatures (SSTs). For the 1982/1983 and 1997/1998 El Niños, there was a meridionally symmetric structure of SST warming with a maximum at the equator. While for 2015/2016 El Niño, there was a meridionally symmetric structure of SST warming with a minimum at the equator.